Spatial scale impact on daily surface water and sediment fluxes in Thukela river, South Africa - Mutema, M.; Jewitt, G.P.W.; Chivenge, Pauline P.; Kusangaya, S.; Chaplot, V. (Elsevier, 2016)
The on- and off-site effects of soil erosion in many environments are well known, but there is still limited understanding of the soil loss fluxes in downstream direction due, among other factors, to scarce and poor quality. A four year study to (i) evaluate water and sediment fluxes at different spatio-temporal scales and (ii) interpret the results in terms of processes involved and the controlling factors, was conducted in Thukela basin, South Africa. Five hierarchically nested catchments; namely microcatchment (0.23 km2), subcatchment (1.20 km2), catchment (9.75 km2), sub-basin (253 km2) and basin (29,038 km2), were used in addition to fifteen (1 m2) microplots and ten (10 m2) plots on five locations within the microcatchment. The results showed 19% decrease of unit-area runoff (q) from 3.1 L m?2 day?1 at microplot to 2.5 L m?2 day?1 at plot scale followed by steeper (56%) decrease at microcatchment scale. The q decreased in downstream direction to very low level (q ? 0.26 L m?2 day?1). The changes in q were accompanied by initial 1% increase of soil loss (SL) from 18.8 g m?2 day?1 at microplot to 19.1 g m?2 day?1 at plot scale. The SL also decreased sharply (by 39 fold) to 0.50 g m?2 day?1 at microcatchment scale, followed by further decrease in downstream direction. The decrease of q with spatial scale was attributed to infiltration losses, while initial increase of SL signified greater competence of sheet than splash erosion. The decrease of SL beyond the plot scale was attributed to redistribution of the soil on the hillslope and deposition on the stream channel upstream of the microcatchment outlet. Therefore, erosion control strategies focussing on the recovery of vegetation on the slope and stabilisation of gullies are recommended.